Peningkatan Kemampuan Pemahaman Konsep Matematika melalui Pendekatan Kontekstual pada Siswa Kelas V MIN 2 Kota Pariaman - Husna, Fitriatul (Journal of Development Education and Learning (JODEL), 2025)
Difficulty in grasping mathematical concepts among primary school students reduces their problem-solving ability and learning motivation. This study addresses conceptual understanding in Grade V students at MIN 2 Kota Pariaman. The study aimed to improve students' conceptual understanding of mathematics through the implementation of a contextual teaching and learning (CTL) approach. This Classroom Action Research (CAR) employed a two-cycle design involving planning, action, observation, and reflection. Participants were 18 Grade V students. Instruments included pre-test and post-tests, observation checklists, and interview guides. Quantitative data were analyzed descriptively (means, percentages), and qualitative data were analyzed thematically. The average pre-test score was 64.72; after Cycle I, the mean rose to 75.55; after Cycle II, the mean reached 85.28. The percentage of students who met the Kriteria Ketercapaian Tujuan Pembelajaran (KKTP) established for the targeted increased markedly across cycles. Observations and interviews revealed increased student engagement, collaborative problem solving, and better ability to relate mathematical concepts to real-life contexts.